Malaria eradication: the economic, financial and institutional challenge - Mills, A; Lubell, Y; Hanson, K (BioMed Central, 2008)
Malaria eradication raises many economic, financial and institutional challenges. This paper reviews these challenges, drawing on evidence from previous efforts to eradicate malaria, with a special focus on resource-poor settings; summarizes more recent evidence on the challenges, drawing on the literature on the difficulties of scaling-up malaria control and strengthening health systems more broadly; and explores the implications of these bodies of evidence for the current call for elimination and intensified control. Economic analyses dating from the eradication era, and more recent analyses, suggest that, in general, the benefits of malaria control outweigh the costs, though few studies have looked at the relative returns to eradication versus long-term control. Estimates of financial costs are scanty and difficult to compare. In the 1960s, the consolidation phase appeared to cost less than $1 per capita and, in 1988, was estimated to be $2.31 per capita (both in 2006 prices). More recent estimates for high coverage of control measures suggest a per capita cost of several dollars. Institutional challenges faced by malaria eradication included limits to the rule of law (a major problem where malaria was concentrated in border areas with movement of people associated with illegal activities), the existence and performance of local implementing structures, and political sustainability at national and global levels. Recent analyses of the constraints to scaling-up malaria control, together with the historical evidence, are used to discuss the economic, financial and institutional challenges that face the renewed call for eradication and intensified control. The paper concludes by identifying a research agenda covering: issues of the allocative efficiency of malaria eradication, especially using macro-economic modelling to estimate the benefits and costs of malaria eradication and intensified control, and studies of the links between malaria control and economic development, the costs and consequences of the various tools and mixes of tools employed in control and eradication, issues concerning the extension of coverage of interventions and service delivery approaches, especially those that can reach the poorest, research on the processes of formulating and implementing malaria control and eradication policies, at both international and national levels, research on financing issues, at global and national levels.